2013
DOI: 10.5152/akd.2013.075
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue: a review of physiology, pathophysiology, and clinical applications

Abstract: Visceral fat tissue is an important predictor of cardio-metabolic diseases, carrying more risk than general fat accumulation. Epicardial fat, a particular form of visceral fat deposited around the heart, is considered an important cardiovascular risk predictor, in view of producing and releasing several adipo-cytokines. There is growing evidence about the physiological and metabolic importance of epicardial fat. Epicardial fat thickness and volume have both strong correlation between obesity, impaired fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 47 publications
1
64
0
3
Order By: Relevance
“…Also, the mean value of two images obtained in the parasternal long-axis and short-axis views should be calculated. Additionally, it would be better to give inter- and intraobserver variability for epicardial adipose tissue measurement in the current study [12]. …”
mentioning
confidence: 99%
“…Also, the mean value of two images obtained in the parasternal long-axis and short-axis views should be calculated. Additionally, it would be better to give inter- and intraobserver variability for epicardial adipose tissue measurement in the current study [12]. …”
mentioning
confidence: 99%
“…; P = 0.008) were higher in the CAD group than in the normal subjects. SAT area was higher in the normal group (176.48 ± 79.56 versus 147.56 ± 56.63 cm 2 ; P = 0.005).…”
Section: Resultsmentioning
confidence: 84%
“…Perivascular EAT surrounding coronary vessels promotes the development of atherogenesis by direct diffusion of various cytokines and free fatty acid (FFA) into the vessel wall and the systemic circulation. 1,2) In contrast, intramyocardial coronary artery segments not in direct contact with EAT rarely contain atherosclerotic plaque. 35) Another possible explanation for the relationship between EAT and CAD is the enhanced infl ammatory responses in EAT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that CACS was significantly correlated with total coronary plaque area (p=0.000 rho=0.997) but not with EFV (p=0.085, rho=0.168). It is known that body mass index affects EFV [22]. Subgroup analysis was carried out for non-obese patients to remove the effect of obesity on EFV (n=72).…”
Section: Discussionmentioning
confidence: 99%